Five New 3,4-Seco-Lanostane-type Triterpenoids with Antiproliferative Activity in Human Leukemia Cells Isolated from the Roots of Kadsura coccinea - Wang, Nan; Li, Zhan-lin; Song, Dan-dan; Li, Wei; Pei, Yue-hu; Jing, Yong-kui; Hua, Hui-ming (Planta Medica, 2012)
Five new 3,4-seco-lanostane-type triterpenoids, seco-coccinic acids G–K (1–5), and a known compound, seco-coccinic F, were isolated from the roots of Kadsura coccinea (Lem.) A. C. Sm. Their structures were elucidated by spectroscopic methods, including 2D-NMR and HR-MS techniques. The cell growth inhibitory effects of these compounds were assayed in human leukemia HL-60 cells, and it was found that 1, 5, and 6 showed antiproliferative effects with GI50 values of 28.4, 15.2, and 16.6 µM, respectively.
Keywords: Kadsura coccinea; Schizandraceae; triterpenoid; antiproliferative activity; leukemia HL-60